2006
DOI: 10.1177/107327480601300206
|View full text |Cite
|
Sign up to set email alerts
|

Poorly Differentiated and Anaplastic Thyroid Cancer

Abstract: Background: Poorly differentiated thyroid carcinoma (PDTC) and anaplastic (undifferentiated) thyroid carcinoma (ATC) comprise a small subset of thyroid tumors that are associated with a poor prognosis and account for Shaha, MD, FACS, Head and Neck Service, Memorial Sloan-Kettering Cancer Center, 1275 York Avenue, New York, NY 10021. E-mail: shahaa@mskcc.org No significant relationship exists between the authors and the companies/organizations whose products or services may be referenced in this article. Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
2
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(143 citation statements)
references
References 93 publications
3
126
2
12
Order By: Relevance
“…The proportions observed regarding the histological types are compatible with those described for thyroid carcinoma (16,18,19). We reported 91% of differentiated tumors (83.7% of papillary carcinomas) in contrast with the rate of 72% reported in an epidemiological study of patients from São Paulo (18). However, our sample should not be considered a representation of the population.…”
Section: Discussioncontrasting
confidence: 49%
“…The proportions observed regarding the histological types are compatible with those described for thyroid carcinoma (16,18,19). We reported 91% of differentiated tumors (83.7% of papillary carcinomas) in contrast with the rate of 72% reported in an epidemiological study of patients from São Paulo (18). However, our sample should not be considered a representation of the population.…”
Section: Discussioncontrasting
confidence: 49%
“…A small subset of these tumors, however, may progress to more aggressive neoplasms such as poorly differentiated and undifferentiated carcinomas. 11,27 Mutations of candidate genes such as TP53 and CTNNB1, the gene encoding b-catenin, and abnormal cell cycle regulation, proliferation, and apoptosis are associated with aggressive neoplasms and have been suggested as markers of thyroid tumor progression. [28][29][30][31][32] Columnar cell carcinoma is a recognized variant of well-differentiated papillary thyroid carcinoma that is associated with an uncertain clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that WDTC progresses to ATC and PDTC as a result of epithelial-mesenchymal transition (EMT) (Zhong et al 2005, Patel & Shaha 2006, which is accompanied by altered cellular morphology and increased cell spreading (De Craene & Berx 2013). Given the findings of low levels of miR-145 in PDTC and ATC, we postulated that miR-145 may mediate EMT and carried out in vitro studies investigating cellular invasion and migration.…”
Section: Mir-145 Regulates Cellular Invasion and Migration And Emt Mmentioning
confidence: 99%